Random Assignment in School Settings: A Systematic Review of Yoga Interventions for Adolescents. - Schelly, David; Watts, Mary Page (Journal of Child & Family Studies, 2025)
Yoga has been studied extensively in school settings, including many randomized controlled trials that suggest a range of benefits for healthy adolescents. Yet these studies face practical methodological challenges, including how to randomly assign children in school. The purpose of this study was to conduct a methodologically rigorous systematic review of school-based yoga interventions with random assignment of healthy adolescents. We incorporated a risk of bias measure to consider the trustworthiness of each study, with a detailed focus on the risk of bias in five domains and an overall classification of risk (high, medium, or low). An electronic database search was conducted for studies published between 2014 and 2024, including CINAHL, PsychNet, PubMed, Science Direct, and Scopus. Randomized trials that provided yoga-based interventions for 10–18-year-old individuals in a school-based setting were included. The search identified 1018 studies, of which 20 met the inclusion criteria and were reviewed. All 20 studies were deemed to entail a high overall risk of bias. Common methodological problems included randomizing by classroom but with a small number of groups, measuring multiple outcomes with limited details about whether the measures would be sensitive to intervention effects, and reporting incomplete or selected results that favored yoga. Better study designs are discussed, focusing on study designs that are feasible with limited budgets. Until well-designed yoga programs are implemented in school settings, it continues to be difficult to find statistically significant results that do not also entail a high risk of bias that impairs the study's trustworthiness.